Cellular 5′-3′ mRNA Exoribonuclease XRN1 Inhibits Interferon Beta Activation and Facilitates Influenza A Virus Replication - Yen-Chin Liu (American Society for Microbiology, 2021)
ABSTRACT Cellular 5′-3′ exoribonuclease 1 (XRN1) is best known for its role as a decay factor, which by degrading 5′ monophosphate RNA after the decapping of DCP2 in P-bodies (PBs) in Drosophila, yeast, and mammals. XRN1 has been shown to degrade host antiviral mRNAs following the influenza A virus (IAV) PA-X-mediated exonucleolytic cleavage processes. However, the mechanistic details of how XRN1 facilitates influenza A virus replication remain unclear. In this study, we discovered that XRN1 and nonstructural protein 1 (NS1) of IAV are directly associated and colocalize in the PBs. Moreover, XRN1 downregulation impaired viral replication while the viral titers were significantly increased in cells overexpressing XRN1, which suggest that XRN1 is a positive regulator in IAV life cycle. We further demonstrated that the IAV growth curve could be suppressed by adenosine 3′,5′-bisphosphate (pAp) treatment, an inhibitor of XRN1. In virus-infected XRN1 knockout cells, the phosphorylated interferon regulatory factor 3 (p-IRF3) protein, interferon beta (IFN-β) mRNA, and interferon-stimulated genes (ISGs) were significantly increased, resulting in the enhancement of the host innate immune response and suppression of viral protein production. Our data suggest a novel mechanism by which the IAV hijacks the cellular XRN1 to suppress the host innate immune response and to facilitate viral replication. IMPORTANCE A novel mechanistic discovery reveals that the host decay factor XRN1 contributes to influenza A virus replication, which exploits XRN1 activity to inhibit RIG-I-mediated innate immune response. Here, we identified a novel interaction between viral NS1 and host XRN1. Knockdown and knockout of XRN1 expression in human cell lines significantly decreased virus replication while boosting RIG-I-mediated interferon immune response, suggesting that XRN1 facilitates influenza A virus replication. The pAp effect as XRN1 inhibitor was evaluated; we found that pAp was capable of suppressing viral growth. To our knowledge, this study shows for the first time that a negative-strand and nucleus-replicating RNA virus, as influenza A virus, can hijack cellular XRN1 to suppress the host RIG-I-dependent innate immune response. These findings provide new insights suggesting that host XRN1 plays a positive role in influenza A virus replication and that the inhibitor pAp may be used in novel antiviral drug development.